Acute Fulminant Fungal Sinusitis in Patients with Acute Leukemia - P Kordbacheh; P Badiee; A Alborzi; F Zaini; H Mirhendi; M Mahmoudi; B Gramizadeh; M Ramzi (Tehran University of Medical Sciences, 2008)
"nBackground: Acute fulminant fungal sinusitis is a rapidly progressive disease with high mortality (50-80%) and occurring with increasing frequency in patients with acute leukemia. The purpose of the present study was early diagnosis of this lethal infection."nMethods: In a cross-sectional study, 142 patients with hematological malignancies were studied immediately by initiation of chemotherapy to determine early clinical and radiological findings of invasive fungal sinusitis. This infection was confirmed by pathological and mycological methods."nResults: Acute fulminant fungal sinusitis was diagnosed in 8 patients with acute leukemia. The most common isolated fungi was Aspergillus flavus (n= 5) followed by Aspergillus fumigatus (n= 2) and Rhizopus sp. (n= 1). Despite prompt surgical and medical therapy, the disease in our patients was very aggressive with a rapid clinical course and high mortality."nConclusion:  The present report shows the poor prognosis of invasive fungal sinusitis in neutropenic patients; the necessity to take intensive preventive measures and the application of new diagnostic methods for early detection of fungal infection in these high risk patients.